Medication regimen complexity and its impact on medication adherence and glycemic control among patients with type 2 diabetes mellitus in an Ethiopian general hospital - Tadesse Awoke Ayele; Asnakew Achaw Ayele; Henok Getachew Tegegn; Mohammed Biset Ayalew (BMJ Open Diabetes Research & Care)
Background Different studies reported that higher diabetes-specific Medication Regimen Complexity Index (MRCI) has a negative impact on glycemic control potentially by decreasing medication adherence. However, information about regimen complexity and its association with adherence and glycemic control in Ethiopian patients with diabetes is unknown.Aim To evaluate medication regimen complexity and to assess its impact on medication adherence and glycemic control among patients with type 2 diabetes Mellitus (T2DM).Methods A hospital-based cross-sectional design was conducted at Debre Tabor General Hospital from 1 May 2018 to 30 June 2018. Medication regimen complexity was evaluated using the 65-item validated tool called Medication Complexity Index (MRCI). Adherence was measured using Morisky Medication Adherence Scale while patients were classified as having poor or good glycemic control based on the recent record of their fasting blood glucose. Multivariable logistic regression analysis was applied to determine the association between predictive variables and outcome variables.Results A total of 275 patients with T2DM who meet the inclusion criteria were included in the final analysis. About 22.2% of the participants were classified as having high diabetes-specific MRCI, whereas 35.6% of the participants were classified as having high patient-level MRCI. The majority (70.5%) of the respondents were adherent to their medications, and 42.9% of the total population were categorized as having good glycemic control. According to the result of the multivariate analysis, patients with low-level and moderate-level MRCI of both diabetes-specific and patient-level MRCI were more adherent to their medication compared with patients with high MRCI. High diabetes medication regimen complexity was associated with poor glycemic control in the adjusted analyses (adjusted OR = 0.276; 95% CI = 0.100 o 0.759).Conclusion The prevalence of high MRCImedication regimen complexity index is high among patients with T2DM. Patients with low and moderate regimen complexity had improved adherence. High diabetes-specific medication regimen complexity was associated with poor glycemic control. Simplification of a complex medication regimen for patients with diabetes should be sought by physicians and pharmacists to improve medication adherence and subsequent improvement in glycemic control.